Enhancing mHealth applications through user-centred design: a conceptual framework for improved healthcare accessibility and user experience / Abdul Hapes Mohammed, Nadia Abdul Wahab and Norfiza Ibrahim - Mohammed, Abdul Hapes; Wahab, Nadia Abdul; Ibrahim, Norfiza (UiTM Cawangan Perlis, 2025)
The rapid growth of mobile health (mHealth) applications offers significant opportunities to improve healthcare delivery. However, the success of these applications largely depends on their alignment with user needs and preferences. This study introduces a conceptual framework cantered around User-Centred Design (UCD) to enhance mHealth applications by prioritizing user experience and accessibility. By focusing on UCD principles, the framework addresses key aspects such as usability, behavioural control, and the influence of subjective norms on user adoption. The framework was developed through qualitative interviews with nine experts from medical and IT fields, each possessing over 15 years of experience. Their insights helped refine the framework to ensure it meets the diverse needs of mHealth users. The UCD approach ensures that the application interface is intuitive, engaging, and tailored to users’ expectations, thereby increasing user satisfaction and adoption rates. By integrating UCD into the mHealth application design process, this framework provides a structured approach to creating more accessible and user-friendly healthcare solutions. This focus on UCD is essential for overcoming the barriers to mHealth adoption, ensuring that applications are not only functional but also resonate with users on a personal level. The proposed framework lays the groundwork for future innovations in mHealth, driving the development of applications that are both effective and widely accepted by users.